POLICY ANALYSIS AND FEABSIBILITY OF CULTURAL VALUES IN RECOGNIZING THE ORIGINAL VILLAGE (CASE STUDY: VILLAGE BAHALAR QUI’IC) VIQUEQUE – TIMOR LESTE, 2017 - Guterres, Salomão Rangel Baptista; Pandie, MS, Dr. David B. W.; Tamunu, SU, Dr. Lenny M (IJRDO - Journal of Social Science and Humanities Research, 2018)
The original village of Bahalar Qui'ic is a past heritage village with original institution structure and local regulations which still maintained by the community.  Elderly or traditional leaders have dominant powers, ranging from the control of agrarian resources and they have absolute right to decide who will as a leader of the village. The original village is not familiar with the concept of citizens (individuals who are placed as whole persons, who have equal rights and obligations), but rather prioritize the common good with the community, by Kurniawan (2013: 248). With the existence of the original village, and  changed structural more modern  in  era   independence based on the Village Law No. 9/2016, the writer  will conduct a research in village Bahalar Qui’ic  regarding to the  “Policy Analysis and the Feasibility of Social and Cultural Values in Recognizing  the  Original Village.  The methodology used in this research   a qualitative descriptive analytical method, with an empirical approach, conceptual approach, Mohammad Nazir (1983: 63), to find out the conditions of indigenous villages, which relate to territories, indigenous communities, the potential of village-managed affairs original, native village apparatus, village governance structures, as important factors that can influence government policy to be recognized.